Dolničarjev lapidarij - Šašel Kos, Marjeta (Arheološki vestnik, 1998)
Thirteen Roman inscribed stone monuments (as well as one fragment short of an inscription), are immured in the Ljubljana cathedral (1701-1706) and seminary building (1708-1713). They are also referred to as the Thalnitscher lapidarium. These are primarily Roman tombstones discovered at Ig or Ljubljana (Emona), two of which are most probably counterfeit, while one is dedication to Hercules. A small fragment lacking an inscription may have belonged to an altar.
Keywords: archaeology; arheologija; Dolničar, Janez Gregor, 1655-1719; epigrafika; epigraphy; lapidaries; lapidariji; Latin inscriptions; latinski napisi; nagrobniki; tombstones